Biomechanical comparison between unilateral and bilateral percutaneous vertebroplasty for osteoporotic vertebral compression fractures: A finite element analysis - Dai, Haowen; Liu, Yang; Han, Qing; Zhang, Aobo; Chen, Hao; Qu, Yang; Wang, Jincheng; Zhao, Jianwu (Frontiers in Bioengineering and Biotechnology, 2022)
Background and objective: The osteoporotic vertebral compression fracture (OVCF) has an incidence of 7.8/1000 person-years at 55–65 years. At 75 years or older, the incidence increases to 19.6/1000 person-years in females and 5.2–9.3/1000 person-years in males. To solve this problem, percutaneous vertebroplasty (PVP) was developed in recent years and has been widely used in clinical practice to treat OVCF. Are the clinical effects of unilateral percutaneous vertebroplasty (UPVP) and bilateral percutaneous vertebroplasty (BPVP) the same? The purpose of this study was to compare biomechanical differences between UPVP and BPVP using finite element analysis. Materials and methods: The heterogeneous assignment finite element (FE) model of T11-L1 was constructed and validated. A compression fracture of the vertebral body was performed at T12. UPVP and BPVP were simulated by the difference in the distribution of bone cement in T12. Stress distributions and maximum von Mises stresses of vertebrae and intervertebral discs were compared. The rate of change of maximum displacement between UPVP and BPVP was evaluated. Results: There were no obvious high-stress concentration regions on the anterior and middle columns of the T12 vertebral body in BPVP. Compared with UPVP, the maximum stress on T11 in BPVP was lower under left/right lateral bending, and the maximum stress on L1 was lower under all loading conditions. For the T12-L1 intervertebral disc, the maximum stress of BPVP was less than that of UPVP. The maximum displacement of T12 after BPVP was less than that after UPVP under the six loading conditions. Conclusion: BPVP could balance the stress of the vertebral body, reduce the maximum stress of the intervertebral disc, and offer advantages in terms of stability compared with UPVP. In summary, BPVP could reduce the incidence of postoperative complications and provide promising clinical effects for patients.